Deformation and fracture initiation of Ni3Al intermetallic single crystal turbine blade. (November 2022) - Paik, Suman; Dutta, B.K.; Naveen Kumar, N.; Tewari, R.
Highlights: A crystal plasticity model incorporating non-Schmid effects along with a continuum damage criterion is employed. Single crystal stress-strain and damage parameters for Ni3 Al are determined by comparing computed and experimental data until failure. Ni3 Al-based edge-crack turbine blade under axial loading is analysed to assess damage accumulation near crack tip. Variation in J i as a function of secondary crystallographic orientations and different crack lengths is estimated. Dependence of J i on crack tip stress triaxiality of edge-crack turbine blade is evaluated. Abstract: The present study deals with the determination of fracture properties of a cracked Ni3 Al-based intermetallic single crystal turbine blade subjected to tensile load. The analysis has been carried out by accounting the effect of microstructure, strain hardening and damage development under monotonic loading. A continuum damage criterion combined with crystal plasticity model incorporating non-Schmid effects was employed to evaluate material damage owing to highly localised deformation. The damage evolution was defined as the function of a microstructure variable. The present coupled model was used to replicate the stress-strain behaviour of Ni3 Al single crystals until material softening due to damage after necking. The model parameters were ascertained by a close match of the computed data with the available experimental data. Using the model, damage evolution near crack tip of a cracked Ni3 Al turbine blade was assessed for randomly varying secondary orientations, while maintaining primary orientations same as that of along the solidification direction. The analysis helped to calculate the fracture initiation toughness ( J i ) of turbine blade for various crystallographic orientations. Combined by damage formulation, analysis was continued to estimate the J i values for different crack lengths in all the cases of orientation. Finally, triaxiality quotient ( q ) was computed to characterise the estimated J i values as a function of crack tip constraints. The approach provides a useful way to analyse orientation dependent fracture behaviour of single crystal components with crack under mechanical loading.